Microstructure and performance of laser cladding 17-4PH-xTiC coatings on harvester blades - Dian Yu Luo; Chunjing Liu; Tianlu Wei; Chao Wang; Hairui Ma; Shichun Jiang (PLoS ONE, 2025)
To address the need for extending the service life of combine harvester blades, this study employs laser cladding technology to prepare 17–4PH-xTiC coatings with varying TiC content on 65Mn steel substrates. The effect of TiC content on the microstructure and properties of the coatings was investigated. Specifically, the microstructure of the coatings was observed by scanning electron microscopy and optical microscopy. X-ray diffraction was used to analyze the phase composition, a Vickers hardness tester measured the hardness, and a friction and wear testing machine evaluated the wear resistance. The coating composition with the optimal performance was selected to prepare reinforced coatings on the surface of harvester blades, followed by field tests. Results indicated that when the TiC content in the coating reached 40%, cracks appeared on the surface, and the number of cracks gradually decreased as laser cladding progressed. The cross-sectional microstructure of the coatings mainly featured columnar crystals, columnar dendrites, cell crystals, and unmelted TiC particles. The proportion of secondary precipitated fishbone-like TiC particles also increased, refining the microstructure. The coatings primarily consisted of α-Fe, TiC, γ-Fe, and Cr 23 C 6 . The average hardness of the 17–4PH-xTiC coatings ranged from 359 HV 0.2 to 556 HV 0.2 . Under room temperature conditions, the primary wear mechanisms of the coatings were oxidative wear and adhesive wear. The wear loss of the 10–40% TiC coatings was reduced by 44.1% to 68.1%, respectively, compared to the substrate (65Mn). Field tests showed that the laser-cladded blades maintained a relatively sharp edge even after harvesting wheat for 120 h, whereas the commercially available heat-treated blades had completely failed. Compared to the commercial blade, the wear of the laser-cladded blade was decreased by 67%. This study successfully applied wear-resistant laser cladding coatings on the surface of harvester blades with small substrate thickness, significantly extending their service life.